The Influence Of Number Of Credit, Growth Of The Number Of Customers, and Capital Adequacy On The Profitability Of LPD In Kintamani District - WIRIASTINI, Ni Luh Putu; RINI, Gst. Ayu Intan Saputra; KAWISANA, Putu Gede Wisnu Permana (Journal of Tourism Economics and Policy, 2021)
Profitability is the ability of a financial institution (company) to earn a profit during a certain period, this study aims to determine whether the amount of credit, growth in the number of customers, and capital adequacy affect the profitability of LPD in Kintamani District. Sampling using purposive sampling method. The population in this study consisted of 61 villages in Kintamani District. The number of samples that meet the criteria are 20 LPDs in Kintamani District. The data analysis method used is multiple linear regression. Based on the results of analysis and hypothesis testing, it was found that the amount of credit did not have a positive effect on the profitability of LPDs in Kintamani District, while the growth in the number of customers had a positive and significant effect, and capital adequacy also had a positive and significant effect on the profitability of LPDs in Kintamani District.